A Nonlinear Switching Mechanism in Quantum Dot and Metallic Nanoparticle Hybrid Systems. Issue 6 (26th May 2013) - Cox, Joel D.; Singh, Mahi R.; von Bilderling, Catalina; Bragas, Andrea V.
<x xml:space="preserve">Abstract</x> Second harmonic generation and two‐photon photoluminescence in CdS quantum dots near metallic nanoparticles are theoretically and experimentally investigated. A control laser field is applied to the hybrid system, which couples with the surface plasmons of the metal nanoparticles. The polarized metal nanoparticles then interact with the quantum dots through dipole–dipole interactions, which enhances the intensity of the second harmonic signal from the quantum dots. The density matrix method is used to numerically simulate the second harmonic signal emitted by the quantum dots. It is found that the enhancement of the second harmonic signal can be switched on and off by changing the control field intensity. Alternatively, the second harmonic signal enhancement can be turned on or off by changing the frequency of the control field. This is an interesting finding which can be used to fabricate nonlinear all optical nanoswitching devices from hybrid systems.